STUDI KINETIKA EKSTRAKSI TEMBAGA DARI BIJIH ENARGIT DALAM LARUTAN ASAM SULFAT - Kostiawan Sukamto; Isal Kamumu; Ahmad Kadir Kilo; Akram La Kilo (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
This study investigates the kinetics of copper extraction from enargite ore (Cu₃AsS₄) using sulfuric acid (H₂SO₄) solution with hydrogen peroxide (H₂O₂) as an oxidizing agent. Leaching experiments were carried out under various operating conditions, including H₂SO₄ concentrations (1, 1.5, and 2 M), H₂O₂ concentrations (1, 1.5, and 3 M), solid percentages (5%, 10%, and 15%), and temperatures (30, 40, and 50 °C), with a leaching time of up to 480 minutes. The results indicated that higher concentrations of H₂SO₄ and H₂O₂ significantly enhanced copper extraction efficiency, while increasing solid percentage reduced the leaching performance. The optimum condition was achieved at 2 M H₂SO₄, 3 M H₂O₂, 5% solids, and 50 °C, resulting in a maximum copper extraction of 97.95%. Kinetic analysis revealed that the leaching process was predominantly controlled by diffusion through a porous product layer based on the shrinking core model, but shifted to interface reaction control at higher temperatures. These findings provide new insights into the leaching mechanism of enargite ore and serve as a foundation for developing more efficient and environmentally friendly hydrometallurgical processes for copper recovery.